Spin-Orbit Photonics in 3D Rotated Anisotropic Materials - Jisha, Chandroth P.; Beeckman, Jeroen; Nolte, Stefan; Alberucci, Alessandro (Optics InfoBase Conference Papers, 2022)
We investigate light propagation in point-wise rotated anisotropic materials, where rotations are non-planar. We demonstrate the emergence of effective electric and magnetic fields -proportional to the gradient of the rotation angle- acting on the photons.
CRIS-Team Scopus Importer:2023-04-20